The Effect of Family and Peer Support on the Occurrence of ODMK (People with Psychiatric Problem) in Adolescents - Aulia Fatmayanti; Kuswanto Kuswanto; Tavip Indrayana (Poltekkes Kemenkes Yogyakarta, 2020)
Mental disorders are very common in adolescents with suicidal behavior. Not all acts of suicide are caused by mental disorders, but 80-90% of adolescents who die from suicide have significant psychopathology such as mood disorders, anxiety disorders, behavioral problems, and drug abuse. Data from the WHO in 2017 about the suicidal behavior of Indonesian youth aged 13-17 as many as 3.9% of adolescents in Indonesia have tried to commit suicide at least once in the last year, 5.6% of adolescents have made plans related to the way they commit suicide and 5.4% of adolescents are considered serious have considered / have suicidal ideas. Mental Health Services for everyone and the guarantee of the rights of People with Psychiatric Problems along with People with Mental Disorders have not been realized optimal. People with mental disorders really need the support of the people closest, especially social support from family. Family support one of the most important healing medicines for patients with mental disorders. Teenagers need to be prepared early on both mentally and spiritually. The purpose wast to determine the effect of family and peer support on the occurrence of people with psychiatric problems in adolescents. The results was most respondents who received support from families did not experience people with psychiatric problems as many as 69 (32.5%) and respondents who lack family support experienced people with psychiatric problems as many as 53 (27.0%) respondents. Most respondents who experienced people with psychiatric problems and lack of peer support were 45 (23.0%) while respondents who received support from peers and experienced people with psychiatric problems were 36 (18.4%). The results of p value 0.480 that there is no significant relationship between peers with people with psychiatric problems and p value 0,000 that there is a significant relationship between family support and people with psychiatric problems.